A model for supply chain planning: Supplier selection and quantity allocation in the case of fixed lot size (2013)
The globalization of production systems has led organizations to consider the supplier management function as a strategic decision. There is significant research work addressing decision making and supplier management. However, there is a lack of research in the case of multiple suppliers with different characteristics and attributes and able to satisfy a product demand defined by a fixed lot size. This kind of demand arises in production environments organized by processes such as the pharmaceutical and food industry. This research aims at fulfilling this lack of research in supplier management. The proposed methodology is based on the formulation of a Mixed Integer Linear Programming model for optimizing the decisions of supplier selection and order quantity allocation in the case of fixed lot size. A numerical example shows the applicability and usefulness of the proposed model. Furthermore, a sensitivity analysis shows that the model is sensitive to changes in parameters. Finally, the results also show that the model is practical and can be easily adapted by organizations that purchase products in fixed-size lots.